Cognitive Performance Profile in Pediatric Moyamoya Disease Patients and Its Relationship With Regional Cerebral Blood Perfusion - Li, Jiaxi; Liu, Xingju; Zhang, Dong; Zhang, Yan; Wang, Rong; Yuan, Jing; Zhao, Jizong (Frontiers in Neurology, 2019)
Object: Moyamoya disease affects the cognitive function of pediatric patients, and compromised cerebral blood flow might be the potential cause. We aimed to explore the specific correlation between cognitive impairment and regional perfusion status in pediatric moyamoya disease patients. Methods: We prospectively enrolled consecutive pediatric moyamoya disease patients admitted to Beijing Tiantan Hospital from July 2017 to March 2019. Arterial spin-labeling magnetic resonance and Wechsler Intelligence Scale for Children (the 4th edition) were performed for all participants. The cognitive performance of patients was analyzed, and its correlation to cerebral perfusion status was also investigated in the region of interest-based analysis. Results: A total of 21 patients met the inclusion criteria (mean aged 11.14 ± 2.82, male: female = 11:10). Six patients (28.6%) showed no cognitive deficits in any index score, while 15 (71.4%) showed cognitive deficits with differing severity. Nine (42.9%) patients showed overall cognitive impairment, and all cognitive index scores except for Verbal Comprehension Index were significantly lower than the mean scores of normative data with corresponding age. Perceptual Reasoning Index (p = 0.019) were statistically lower in patients with radiologically confirmed cerebral infarction. Suzuki stage of the left hemisphere negatively correlated to Full-scale Intelligence Quotient (r = -0.452, p = 0.039). Region of interest analysis showed that cerebral blood flow of left temporal lobe independently associated with the Processing Speed Index (β = 0.535, p = 0.041). Conclusion: Pediatric moyamoya disease patients exhibited different levels of cognitive impairment. Cerebral infarction is related to poorer perceptual reasoning ability. Cerebral blood flow in left temporal lobe positively correlates with processing speed.